PERBANDINGAN EFEKTIVITAS PIRASETAM DAN SITIKOLIN PADA PASIEN STROKE ISKEMIK DI BANGSAL RAWAT INAP RSUD UNDATA PALU - , ELVIA A.Y ALHUSNI; , Prof. Zullies Ikawati, Ph.D., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Stroke is a cerebrovascular disease that causes neurologic damage. One of therapies to repair neurologic function is neuroprotectant. Neuroprotectant drugs such as piracetam and citicoline usually used by ischemic stroke patients are still controversial and raise arguments against scientific research. Meanwhile at Undata Hospital Palu piracetam and citicoline are mostly used by ischemic stroke patients either individually or both combined. The objective of the study was to identify effectiveness of piracetam and citicoline using The National Institute of Health Stroke Scale (NIHSS) in ischemic stroke patients at inpatient ward of Undata Hospital Palu during October 2012 to January 2013. The study was experimental with RCT-Parallel design (Randomized Controlled Clinical Trial) using single blind trials. Data were collected prospectively